Tumor-infiltrating lymphocytes in patients with HER2-positive breast cancer treated with neoadjuvant chemotherapy plus trastuzumab, lapatinib or their combination: A meta-analysis of randomized controlled trials. (June 2017) - Solinas, C.; Ceppi, M.; Lambertini, M.; Scartozzi, M.; Buisseret, L.; Garaud, S.; Fumagalli, D.; de Azambuja, E.; Salgado, R.; Sotiriou, C.; Willard-Gallo, K.; Ignatiadis, M.
Highlights: This is a meta-analysis of neoadjuvant randomized studies investigating TIL in HER2-positive breast cancer. High baseline TIL are associated with increased probability of pCR in HER2-positive breast cancer. No interaction with the anti-HER2 backbone (trastuzumab, lapatinib or their combination) was observed. No interaction with the chemotherapy backbone (anthracyclines plus taxanes vs. taxanes) was observed. Abstract: Background: A relationship between baseline tumor-infiltrating lymphocytes (TIL) and outcomes has been described in HER2-positive breast cancer. Nevertheless, the magnitude of this association and whether this effect differs based on the type of anti-HER2 agent remain controversial. This meta-analysis investigated the association between baseline TIL and pathologic complete response (pCR) rates in HER2-positive breast cancer patients treated with neoadjuvant chemotherapy plus trastuzumab and lapatinib either alone or in combination. Methods: A literature search covering PubMed, Embase and the Cochrane library up to October 31, 2016 identified randomized, controlled trials investigating neoadjuvant chemotherapy plus trastuzumab and lapatinib either alone or in combination where published data for pCR based on pre-treatment TIL scores were available. Two subgroups were considered: high baseline TIL vs. non-high TIL, according to each study definition. Summary risk estimates (odds ratio) and 95% confidence intervals (CI) were calculated for pCR using pre-treatment TIL levels for each trial. Pooled analyses were conducted using random and fixed effects models. Interaction P -values were computed using a Monte Carlo permutation test. Results: A total of 5 studies ( N = 1256 patients) were included. Overall, high TIL subgroup was associated with a significantly increased pCR rate (OR 2.46; 95% CI 1.36–4.43; P = 0.003). No interaction was observed between TIL subgroup (high vs. non-high TIL) and response to anti-HER2 agent(s) (trastuzumab vs. lapatinib vs. their combination; P = 0.747) and chemotherapy (anthracycline and taxanes vs. taxanes only; P = 0.201). A stronger association between high TIL subgroup and pCR rates was observed when examining only the 4 studies using anthracycline- and taxane- based neoadjuvant chemotherapy and the 60% cut-off for high TIL ( N = 869, NeoALTTO excluded) with an OR of 2.88 (95% CI 2.03–4.08; P < 0.001). Conclusions: In HER2-positive breast cancer, high baseline TIL are associated with increased pCR probability irrespective of neoadjuvant anti-HER2 agent(s) and chemotherapy regimens used.